2019
DOI: 10.1111/jfd.13077
|View full text |Cite
|
Sign up to set email alerts
|

Aeromonas salmonicida infects Atlantic salmon (Salmo salar) erythrocytes

Abstract: Aeromonas salmonicida subsp. salmonicida (hereafter A. salmonicida) is the aetiological agent of furunculosis in marine and freshwater fish. Once A. salmonicida invade the fish host through skin, gut or gills, it spreads and colonizes the head kidney, liver, spleen and brain. A. salmonicida infects leucocytes and exhibits an extracellular phase in the blood of the host; however, it is unknown whether A. salmonicida have an intraerythrocytic phase. Here, we evaluate whether A. salmonicida infects Atlantic salmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…A similar phenomenon was observed by Drangsholt et al (2011) for Furunculosis, another important disease in Atlantic salmon 38 . This disease is caused by Aeromonas salmonicida, a facultative intracellular bacteria that, similar to P. salmonis, has the ability to infect and replicate in host cells in order to bypass the host defense mechanisms 39,40 . Thus, similar to Drangsholt et al, our results indicate that not all resistant fish selected in an environment without vaccination will be resistant following vaccination 38 .…”
Section: Discussionmentioning
confidence: 99%
“…A similar phenomenon was observed by Drangsholt et al (2011) for Furunculosis, another important disease in Atlantic salmon 38 . This disease is caused by Aeromonas salmonicida, a facultative intracellular bacteria that, similar to P. salmonis, has the ability to infect and replicate in host cells in order to bypass the host defense mechanisms 39,40 . Thus, similar to Drangsholt et al, our results indicate that not all resistant fish selected in an environment without vaccination will be resistant following vaccination 38 .…”
Section: Discussionmentioning
confidence: 99%
“…V. anguillarum bacterin was labeled with 5-([4,6-dichlorotriazinyl] amino) fluorescein hydrochloride (DTAF; Sigma) according to previously described protocols [ 40 ] with minor modifications. First, V. anguillarum bacterin (~1 × 10 10 CFU mL −1 ) was centrifuged at 4200× g for 10 min and then resuspended in 950 µL of bicarbonate buffer (0.1 M, pH 9).…”
Section: Methodsmentioning
confidence: 99%
“…Molecular studies have showed higher expression of pro-inflammatory genes, such as TLR5M, TLR5S, GATA3, IFN-γ, IL-17D, as well as the pleiotropic cytokine gene IL-10 in infected Atlantic salmon [33]. Interestingly, recent findings have showed an intraerythrocytic phase of A. salmonicida during the infection [34]. Overall, the importance of Atlantic salmon iron homeostasis regulation is well reported during these pathogens' infection [15,17,35,36].…”
Section: Introductionmentioning
confidence: 94%